One‐year analysis of Elekta CBCT image quality using NPS and MTF - Nakahara, Satomi; Tachibana, Masayuki; Watanabe, Yoichi (Journal of Applied Clinical Medical Physics, 2016)
The image quality (IQ) of imaging systems must be sufficiently high for image‐guided radiation therapy (IGRT). Hence, users should implement a quality assurance program to maintain IQ. In our routine IQ tests of the kV cone‐beam CT system (Elekta XVI), image noise was quantified by noise standard deviation (NSD), which was the standard deviation of CT numbers measured in a small area in an image of an IQ test phantom (Catphan), and the high spatial resolution (HSR) was evaluated by the number of line‐pairs (LPN) visually recognizable in the image. We also measured the image uniformity, the low contrast resolution, and the distances of two points for geometrical accuracy. For this study, we did an additional evaluation of the XVI data for 12 monthly IQ tests by using noise power spectrum (NPS) for noise, modulation transfer function (MTF) for HSR, and CT number‐to‐density relationship. NPS was obtained by applying Fourier analysis in a small area on the uniformity test section of Catphan. The MTF analysis was performed by applying the Droege‐Morin (D‐M) method to the line‐pair bar regions in the phantom. The CT number‐to‐density relationship was obtained for insert materials in the low‐contrast test section of the phantom. All the quantities showed a noticeable change over the one‐year period. Especially the noise level improved significantly after a repair of the imager. NPS was more sensitive to the IQ change than NSD. MTF could provide more quantitative and objective evaluation of HSR. The CT number was very different from the expected CT number, but the CT number‐to‐density curves were constant within 5% except for two months. Since the D‐M method is easy to implement, we recommend using MTF instead of LPN even for routine QA. The IQ of the imaging systems was constantly changing; hence, IQ tests should be periodically performed. Additionally, we found the importance of IQ tests after every service work, including detector calibration as well as preventive maintenance. PACS number(s): 87.56Da, 87.57.C‐, 87.57.N‐, 8757.Q‐